Attitudes and behaviors regarding online pharmacies in the aftermath of COVID-19 pandemic: At the tipping point towards the new normal - Fittler, András; Ambrus, Tünde; Serefko, Anna; Smejkalová, Lenka; Kijewska, Anna; Szopa, Aleksandra; Káplár, Mátyás (Frontiers in Pharmacology, 2022)
The COVID-19 pandemic accelerated the online purchase of goods and services in which today’s e-pharmacy is now an integral part of healthcare provisions in developed countries. The aim of our research was to assess the frequency and attitudes of European consumers purchasing medications online prior to and following the pandemic in the Visegrad Group countries (V4). An online cross-sectional study was conducted between May-August 2022. A 25-item questionnaire with single choice and 5-point Likert scale answers was used and implemented in Google forms and Pollfish. A sampling of 2087 responses were collected. A majority (92.8%) of the respondents were aware medicines can be purchased online, yet prefer traditional pharmacies (4.6±0.8) and somewhat oppose the internet channel (2.8±1.3). Following the outbreak of COVID-19 pandemic, respondents’ attitude towards purchasing consumer goods (3.65±0.89) and medications (3.26±0.91) online increased, however, the change regarding medications is significantly smaller (p<0.01). A distinct increase in the frequency of buying medicines (from 49.16% to 55.48%) and health products (from 60.61% to 63.0%) online was measured since the breakout of the COVID-19 pandemic (p<0.05). Despite the relatively high prevalence witnessed in previous purchases, our results highlight the trend in which 18.3% of participants will definitely purchase medications online while a proportionate 17.7% will not in the future. Although long-term post-COVID attitudes towards the internet pharmacy channel has modestly increased, in comparison to previously published research the frequency of purchasing medications online has significantly increased during the past years. As national legislation in V4 countries permit only non-prescription online sales, our findings are primarily applicable to countries with similar regulatory environment. The rapid global spread of the coronavirus has transitionally affected medicinal purchase behaviors, augmenting potential public health concerns related to online sourcing. Consequently, public awareness campaigns are needed to promote verified online pharmacies and prevent the utilization of illicit websites and the use of unregistered, substandard and falsified medicinal products.